2006
DOI: 10.1021/jo060102t
|View full text |Cite
|
Sign up to set email alerts
|

Solvent- and Temperature-Tuned Orientation of Ferrocenyl Azide Inside β-Cyclodextrin

Abstract: An induced circular dichroism (ICD) solution study on the orientation of ferrocenyl azide within the beta-cyclodextrin cavity is described. In DMSO, ferrocenyl azide prefers an axial inclusion, whereas in ethylene glycol and DMSO/H2O = 50/50 an equatorial alignment dominates. As shown by temperature-dependent ICD spectra, at lower temperatures ferrocenyl azide adopts preferentially an equatorial arrangement, whereas at higher temperatures an axial one is favored. Temperature and solvent effects on the co-confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In compound 3, the azide groups were found to be nonlinear and were found to lie away from the plane of the Cp ring. The bond angle N1eN2eN3 was found to be 167.8 (8) whereas the same bond angle in the ferrocenyl azide was 172.9(1) [32].…”
Section: Resultsmentioning
confidence: 90%
“…In compound 3, the azide groups were found to be nonlinear and were found to lie away from the plane of the Cp ring. The bond angle N1eN2eN3 was found to be 167.8 (8) whereas the same bond angle in the ferrocenyl azide was 172.9(1) [32].…”
Section: Resultsmentioning
confidence: 90%
“…These authors also demonstrated that certain hydrocarbons are very soluble in a DMSO/water mixture, and are more strongly bonded to -CD that in the water. Recently, Brinker and coworkers [19] informed a change of the orientation of a guest, azide substituted ferrocene, inside the -CD, by changing the solvent and the temperature. Some authors presently consider that the equilibrium constants may change as a result of competition processes between the guest and the organic solvent [20].…”
Section: Introductionmentioning
confidence: 99%
“…We have studied the literature sources which shows that β‐CD not only have a tendency to form complexes with substrate in aqueous media but also has ability of forming complexes in nonaqueous media like dimethyl sulfoxides (DMSO), DMF, acetonitrile etc. through supramolecular interaction.…”
Section: β‐Cyclodextrin Catalyzed Organic Transformationsmentioning
confidence: 99%